2011
DOI: 10.1091/mbc.e11-05-0467
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated regulation of sulfur and phospholipid metabolism reflects the importance of methylation in the growth of yeast

Abstract: The sulfur assimilation and phospholipid biosynthesis pathways interact metabolically and transcriptionally. Genetic analysis, genome-wide sequencing, and expression microarrays show that regulators of these pathways, Met4p and Opi1p, control cellular methylation capacity that can limit the growth rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 65 publications
1
51
0
1
Order By: Relevance
“…Interestingly, transcription of these genes was also repressed by methionine (Figure 3B). Our observations on the transcriptional coordination between phospholipid synthesis and sulfur metabolism are consistent with previous reports (Hickman et al, 2011; Sadhu et al, 2014). …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, transcription of these genes was also repressed by methionine (Figure 3B). Our observations on the transcriptional coordination between phospholipid synthesis and sulfur metabolism are consistent with previous reports (Hickman et al, 2011; Sadhu et al, 2014). …”
Section: Resultssupporting
confidence: 93%
“…The findings that PE methylation regulates plasma homocysteine and the excretion levels of homocysteine from hepatocytes (Vance, 2014) implicate a function for PE methylation in sulfur metabolism. Moreover, studies in yeast have linked the synthesis of phospholipids to the transcriptional regulation of sulfur metabolic genes (Hickman et al, 2011; Sadhu et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that met4 Δ mutants grow poorly even when supplemented with methionine. However, the addition of SAM restored normal growth rates, suggesting that SAM levels are rate-limiting for supporting maximal growth rates (Hickman et al, 2011). Lastly, ~1% of yeast and mammalian gene products encode SAM-dependent methyltransferases (Petrossian and Clarke, 2011), and this number does not include enzymes that utilize SAM via other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of Cbf1 to upstream sites is required for binding of the ISW2 chromatin-remodeling complex, which is also required for full INO1 derepression (Shetty and Lopes, 2010). Cbf1p also interacts with Met4p, a transcriptional activator in the sulfur assimilation pathway, which is required for activation of genes, including SAM1 and SAM2 , described above, which are required for maintaining levels of Sadenosyl methionine (SAM) (Hickman et al, 2011; Petti et al, 2012), the methyl donor in the phospholipid methylation reactions catalyzed by Cho2p and Opi3p in the synthesis of PC from PE (Fig. 1).…”
Section: Biosynthesis Of Inositol In S Cerevisiae: Biochemistry mentioning
confidence: 99%
“…1). Whereas Met4p is required for SAM2 activation, Opi1p is a direct repressor of SAM2 (Hickman et al, 2011). …”
Section: Biosynthesis Of Inositol In S Cerevisiae: Biochemistry mentioning
confidence: 99%